Analisis Tokoh dan Penokohan dalam Novel Cinta Kala Perang Karya Masriadi Sambo - Tia Sattari; Mukhlis Mukhlis; Rostina Taib (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This study entitled "The Ability of Middle School Students in Banda Aceh in Answering the Problems of Higher Order Thingking Skills (HOTS) on Indonesian Language Learning". The problem this study is how the ability of junior high schoolstudents throughout Banda Aceh in answering the questions Higher Order Thinking Skills (HOTS) in learning Indonesian. The purpose of this study is that researchers can determine the ability of junior high school students throughout the city of Banda Aceh in answering questions on Higher Order Thinking Skills (HOTS) in learning Indonesian. Population of this study was the eighth grade students the three junior high schools in Banda Aceh, namely the State Middle School 1 Banda Aceh, the State Middle School 2 Banda Aceh, and the State Middle School 18 Banda Aceh academic year 2018-2019. Students from the three junior high schools numbered 598 people and sample of this study was 66 students. The method used in this research quantitative descriptive method. This research data was collected through test techniques. Analyzing data using simple statistical techniques that are quantitative. The results showed that the ability students to answer the questions Higher Order Thinking Skills (HOTS) was 42 and included in the less category. The average score obtained by students, namely (a) Junior high school 1 Banda Aceh received a score of 52 included in the less category (b) Junior high school 2 Banda Aceh received a score of 54 and was included in the category of less, (c) Junior high school 18 Banda Aceh received a score 30 and included in the Less category. The conclusions of this study indicate that junior high school students throughout the city of Banda Aceh have not been able to answer the questions Higher Order Thinking Skills (HOTS) in learning Indonesian.